2017
DOI: 10.1016/j.cell.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Complement-Related Regulates Autophagy in Neighboring Cells

Abstract: SUMMARY Autophagy degrades cytoplasmic components and is important for development and human health. Although autophagy is known to be influenced by systemic intercellular signals, the proteins that control autophagy are largely thought to function within individual cells. Here we report that Drosophila Macroglobulin complement-related (Mcr), a complement orthologue, plays an essential role during developmental cell death and inflammation by influencing autophagy in neighboring cells. This function of Mcr invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 56 publications
2
44
0
Order By: Relevance
“…Given recent findings about the complement system in D. melanogaster regulating autophagy in neighboring cells, perhaps antimicrobial autophagy responses might even be established in a cell nonautonomous fashion. 47 C. elegans also uses xenophagic elimination of intracellular microbes, and autophagy machinery can be targeted to virulence factors secreted by extracellular microbes invading this organism. The B. thuringiensis Cry5B PFT disrupts host cell membrane integrity and is then endocytosed as part of the host membrane-repair process.…”
Section: Discussionmentioning
confidence: 99%
“…Given recent findings about the complement system in D. melanogaster regulating autophagy in neighboring cells, perhaps antimicrobial autophagy responses might even be established in a cell nonautonomous fashion. 47 C. elegans also uses xenophagic elimination of intracellular microbes, and autophagy machinery can be targeted to virulence factors secreted by extracellular microbes invading this organism. The B. thuringiensis Cry5B PFT disrupts host cell membrane integrity and is then endocytosed as part of the host membrane-repair process.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in Drosophila have identified factors that are specifically necessary for autophagy in the dying salivary gland, but not for survival-associated starvationinduced autophagy in the larval fat body. These include the cell surface engulfment receptor Draper (drpr) (McPhee et al, 2010), its presumed activating ligand, macroglobulin complement-related (mcr) (Lin et al, 2017), and the Ral GTPase and all subunits of its effector, the exocyst complex (Tracy et al, 2016). Whether the role of these factors can be generalized to other systems of ADCD, specifically in mammals, is unknown.…”
Section: Death-specific Autophagy Factorsmentioning
confidence: 99%
“…The expression patterns of Tep1‐4 have been documented by in situ hybridization . The exact function of each Tep in host defense remains poorly understood despite several studies and their potential role as opsonins has not been definitely determined . Although an initial study failed to reveal a role of Tep1 , Tep2 , Tep3 , or Tep4 in several infection models, even when Tep2‐Tep3‐Tep4 triple mutants were assayed , a quadruple Tep1‐Tep2‐Tep3‐Tep4 mutant was reported to be sensitive to some fungal and Gram‐positive bacterial infections, likely because Toll pathway activation is impaired in this quadruple mutant .…”
Section: Introductionmentioning
confidence: 99%